O08.5 Barriers and facilitators to engagement in the hiv prevention cascade among lesbian, gay, bisexual, and transgender persons in swaziland. (8th July 2017) - Logie, Carmen; Perez-Brumer, Amaya; Jenkinson, Jesse; Madau, Veli; Nhlengethwa, Winnie; Baral, Stefan; Newman, Peter A.
Abstract : Introduction: Swaziland has the highest national adult HIV prevalence globally at 28.8%. Given the criminalization of same-sex practices, there is limited data on the experiences of lesbian, gay, bisexual and transgender (LGBT) persons' engagement with HIV prevention and treatment services. Research is urgently needed to understand barriers and facilitators experienced by LGBT people in Swaziland to engaging with the HIV prevention cascade. Methods: We conducted in-depth interviews with gay, bisexual and other men who have sex with men (MSM) (n=23), lesbian, bisexual and other women who have sex with women (WSW) (n=16), and transgender persons (n=12) in Mbabane and Manzini, Swaziland. Semi-structured interviews, conducted in siSwati, explored experiences of stigma and discrimination, and attitudes and behaviours regarding HIV prevention. Audio files were transcribed verbatim, translated to English, and analysed using thematic techniques. Results: Participants (n=51; mean age: 26.5) identified as gay or lesbian (n=40, 78.4%) and bisexual (n=11, 22.6%). Stigma and discrimination targeting LGBT persons, institutionalised in HIV and other healthcare services, presented significant barriers to HIV prevention, including: mistreatment by healthcare staff, lack of confidentiality, lack of awareness and knowledge of LGBT medical needs, and disallowing intimate partners from accompanying HIV/health care visits. Participants revealed coping strategies and resiliency in navigating these barriers: agency (i.e., self-love), community-level social support, and education. Conclusion: LGBT narratives highlight the importance of community-level support as a strategy to overcome barriers to HIV prevention engagement in Swaziland. However, emergent resiliency strategies are constrained by structural factors rooted in stigma and discrimination. Moreover, these data underscore the importance of implementing evidence-based HIV prevention strategies that mitigate stigma to overcome barrier to service provision and engendering self-worth to facilitate uptake for marginalised communities.